Therapeutic approaches to early intervention in audiology: A systematic review. (November 2021) - Casoojee, A.; Kanji, A.; Khoza-Shangase, K.
Abstract: Babies born with a congenital sensorineural hearing impairment or acquire early-onset permanent bilateral hearing impairment are at risk for delayed speech and language development and poor scholastic outcomes. Auditory Verbal Therapy (AVT) has become the primary intervention approach for developing spoken language in children with hearing impairment, and South Africa also has adopted this approach. The outcomes of AVT within the South African context have not been thoroughly investigated. As part of a larger study, the objective of this systematic review was to describe the speech, language and scholastic outcomes of hearing-impaired children enrolled in AVT as a therapeutic approach to early intervention. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Electronic databases searched included Google Scholar, Science Direct and PubMed. Selected studies were published in English and focused on the outcomes of early intervention for children with hearing impairment. The selected date range of the included articles ensured that the latest research was reviewed. Due to the limited evidence base, the review cannot conclude definitively that AVT yields positive speech, language, and scholastic outcomes in children with hearing impairment. Of the reviewed articles, only one study compares the outcomes of therapeutic intervention approaches, an important consideration, particularly in Low- and Middle-Income countries (LMICs). Current findings provide a strong rationale for the larger study by highlighting that further research comparing AVT to standard speech-language habilitation is required. Research in contexts with linguistic and cultural diversity in countries such as South Africa is required.